Polarization Anisotropy of Photoluminescence Spectra in Gallium Arsenide under Different Surface Waves (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the dynamic polarization anisotropy of photoluminescence spectra  in gallium arsenide under different surface waves configurations by applying  microscopic photoluminescence setup. We have found a periodic emission energy  oscillation due to the strain induced band gap modulation. Time related polarization  anisotropy spectra obtained under the one dimensional standing surface acoustic  waves revealed that the photoluminescence polarization anisotropy became the  stronger when the band gap energy reached its minimum value and that the  polarized direction was perpendicular to the surface acoustic wave propagating  direction. We have also found that the time resolved photoluminescence spectra  from the dynamic quantum dots exhibited emission energy oscillations similar to the  results for the one dimensional standing surface acoustic waves, while no  polarization anisotropy appeared. It was also found that dynamic quantum dots  formed by the two dimensional surface acoustic waves due to interference between  two orthogonally propagating surface acoustic wave beams. The obtained results  were compared with previously obtained results.